VD_FINDINFO Décision / 2013 / 190 vom 25. Januar 2007 - VD Tribunal cantonal (2007)
LIBÉRATION CONDITIONNELLE, MESURE THÉRAPEUTIQUE INSTITUTIONNELLE, INDEMNITÉEN GÉNÉRAL, DÉFENSE D'OFFICE | 59 CP, 62d CP, 26 LEP, 38 LEP, 135 CPP (CH), 393 CPP (CH)